Medical Imaging 2009: Computer-Aided Diagnosis 2009
DOI: 10.1117/12.811336
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing pulmonary nodule shape using a boundary-region approach

Abstract: Using computer-calculated features to characterize the shape of suspicious lesions aims to assist the diagnosis of pulmonary nodules; moreover, these computerized features have to be in agreement with radiologists' ratings measuring their human perception of the nodules' shape. In the Lung Image Database Consortium (LIDC), there exists strong disagreement among the radiologists on the ratings of the shape diagnostic characteristics as well as on their drawn outlines of the extent of the nodules. Since shape is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…3D algorithm [6] analyzed pulmonary nodule characteristics in three-dimensional angle, the algorithm has high algorithm complexity and slow processing time, and it did not establish a unified three-dimensional detection model. GRAD (gradient) algorithm [7] used gradient directionality to discriminate pulmonary nodule characteristics, which has faster speed. RETR (retrieval) algorithm [16] established a retrieval model from the aspect of image information to identify pulmonary nodule characteristics, which has certain discriminating effects.…”
Section: B Comparision Of Signs Discriminant Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D algorithm [6] analyzed pulmonary nodule characteristics in three-dimensional angle, the algorithm has high algorithm complexity and slow processing time, and it did not establish a unified three-dimensional detection model. GRAD (gradient) algorithm [7] used gradient directionality to discriminate pulmonary nodule characteristics, which has faster speed. RETR (retrieval) algorithm [16] established a retrieval model from the aspect of image information to identify pulmonary nodule characteristics, which has certain discriminating effects.…”
Section: B Comparision Of Signs Discriminant Algorithmsmentioning
confidence: 99%
“…Raicu et al [6] constructed a three-dimensional model and then qualitatively judged the characteristics. Horsthemke et al [7] distinguished pulmonary nodules characteristics from gradient directionality. Dhara et al [8] used Gaussian and mean curvature to discriminate characteristics based on differential theory.…”
Section: Introductionmentioning
confidence: 99%
“…Radiologists consider several diagnostic characteristics (namely spiculation, lobulation, sphericity, margin sharpness, and texture etc.) for differentiation of benign and malignant nodules [4–6]. Dhara et al [7] developed several differential geometry‐based techniques for computation of several shape‐based features such as spiculation, lobulation, and sphericity.…”
Section: Introductionmentioning
confidence: 99%
“…New shape features that included Fourier-based descriptors, a variant of the radial gradient index, and a radial normal index were used to predict semantic ratings, including spiculation [11,25]. The authors reported no improvement in predicting semantic ratings, also citing the extent of radiologist disagreement as the primary cause of the poor classification performance.…”
Section: Related Workmentioning
confidence: 99%
“…Since high inter-observer variation was the primary cause of poor classifier performance cited in several of the studies [6,7,10,11,24,25,28], we propose a new approach of first filtering out inter-observer variation in order to reveal fundamental relationships between shape features and the semantic concept of spiculation. In this context, unlike studies that have as their goal demonstrating the complete performance of a CAD system, we are looking into gaining fundamental insight into the shape feature calculations.…”
Section: Related Workmentioning
confidence: 99%